Odpowiedzialność Unii Europejskiej za naruszenie postanowień umowy stowarzyszeniowej — uwagi w świetle orzecznictwa Trybunału Sprawiedliwości - Kalicka-Mikołajczyk, Adriana (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The European Union EU is responsible for consequences of its international actions. However, the material scope of the EU international responsibility depends on the division of competences between the EU and its member states. Each could be held responsible only within the scope of its competences. In cases where the division of powers was not clarified at the time of the negotiation and conclusion of such an agreement, there is joint responsibility, which means that the EU and its member states are jointly liable for fulfilling the obligations owed to a third state under a bilateral association agreement. Since association agreements concluded by the EU are binding on its institutions and on the member states, it is incumbent on both the institutions and the member states to ensure that the obligations arising under such agreements are complied with. In doing so, member states fulfil, “an obligation not only in relation to the third country concerned but also and above all in relation to the Union which has assumed responsibility for due performance of the agreement” C-13/00, Commission of the European Communities v. Ireland, EU:C:2002:184.
Keywords: odpowiedzialność międzynarodowa; umowa stowarzyszeniowa; umowa mieszana